From Post-Fordism to Data Capitalism: A Critical Analysis of Cognitive and Networks Economics in the Film “The Great Hack” - Agus Rahmat Hidayat; Prahastiwi Utari; Sri Hastjarjo (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2025)
Using an analysis of the film “The Great Hack,” this paper aims to examine the economic transformation of society from the post-Fordist era to the information society. The film reveals how data and information have become key commodities in today's digital age, impacting various aspects of social and economic life. The film “The Great Hack” serves as the main case study in this research, which uses a qualitative approach. Content analysis and critical discourse analysis are the instruments used in this study. This method involves reading literature on relevant economic and social theories, as well as conducting a critical analysis of the film's content and message. This research uses the theoretical frameworks of post-Fordism, network society, cognitive capitalism, and information society to study the forms of economic change that have occurred. The results of the study show that the film “The Great Hack” adopts the principles of post-Fordism that have developed in the digital context, resulting in a network society, the concept of cognitive capitalism, and a network society where data is the main resource. In conclusion, the film shows how the principles of post-Fordism have developed in the digital context, resulting in a network society, the concept of cognitive capitalism, and a network society in which data is the primary resource. The practices of Cambridge Analytica demonstrate cognitive capitalism, which shows that economic value comes from knowledge and information.